2019
DOI: 10.1177/0300060519882559
|View full text |Cite
|
Sign up to set email alerts
|

Association between ACE A240T polymorphism and cancer risk: a meta-analysis

Abstract: Objectives The relationship between the A240T polymorphism in the angiotensin-converting enzyme ( ACE) gene and cancer risk remains controversial. Therefore, we conducted a meta-analysis of relevant studies from the published literature. Methods We comprehensively searched available databases to identify eligible studies on the relationship of ACE A240T polymorphism with cancer risk. We calculated pooled odds ratios (OR) with 95% confidence intervals (CI) and then evaluated heterogeneity and publication bias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…However, after removing articles deviating from HWE, the heterogeneity was removed for stratification analysis, suggesting that studies deviating from HWE were a significant source of the heterogeneity. 19 This current meta-analysis had several limitations. First, only articles published in English-language journals were included, with unpublished or non-English-language Table 3.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, after removing articles deviating from HWE, the heterogeneity was removed for stratification analysis, suggesting that studies deviating from HWE were a significant source of the heterogeneity. 19 This current meta-analysis had several limitations. First, only articles published in English-language journals were included, with unpublished or non-English-language Table 3.…”
Section: Discussionmentioning
confidence: 96%
“…However, after removing articles deviating from HWE, the heterogeneity was removed for stratification analysis, suggesting that studies deviating from HWE were a significant source of the heterogeneity. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The D allele might affect renin-angiotensin pathway activity by increasing the serum or local level of ACE, leading to damage of the vascular endothelium and lung epithelium [23]. Studies have shown that some ACE polymorphisms are associated with Alzheimer's disease (the II and ID ACE genotypes), cardiovascular disease (DD), hepatitis C virus (HCV) infection (DD), and cancers (ACE A240T polymorphism) [24][25][26][27][28][29] (Table 1). Itoyama et al found that the frequency of the D allele in SARS patients (with and without hypoxemia) was significantly higher than in healthy controls [21].…”
Section: Angiotensin-converting Enzyme 1 and Angiotensin-converting Enzyme 2 Polymorphismsmentioning
confidence: 99%
“…Some single nucleotide polymorphisms (SNPs) in cancer-related genes have been found to affect cancer risk. 1 3 …”
Section: Introductionmentioning
confidence: 99%
“…Some single nucleotide polymorphisms (SNPs) in cancer-related genes have been found to affect cancer risk. [1][2][3] The metallothionein 2A (MT2A) gene located at chromosome 16q13 is a member of the metallothionein gene family. 4 The protein encoded by MT2A can interact with that encoded by the homeobox containing 1 gene (HMBOX1) in vascular endothelial cells, controlling intracellular zinc levels and affecting apoptotic and autophagy pathways.…”
Section: Introductionmentioning
confidence: 99%